Bencana Kabut Asap Sebagai Dampak Budaya Konsumsi dalam Cerpen “Yang Datang dari Negeri Asap” - Wahyuni, Dessy (UI Scholars Hub, 2021)
Literature, as a work containing facts and fiction, can obscure the conventions of realities and create new realities so that there are no visible boundaries between the real thing and the unreal thing. Fact and fiction coincide and simulate to form hyperreality. In the short story “Yang Datang dari Negeri Asap (Who Comes from the Smoky Country)” by Hary B. Kori’un, the existence of facts and fiction overlap each other. The author created the country of smoke as a fictitious world due to his contemplation on the consumption culture, which is a phenomenon in people’s lives and relates it to the haze disaster that keeps going to occur every year. The researcher sorts out facts and fiction that are interconnected in the short story to explore the creation of hyperreality using the perspective of Jean Baudrillard. As a result, the researcher found a consumption culture in the community, especially plantation entrepreneurs. The presence of a new world in a short story is a reproduction of the value of a sign or symbol that simulates as if there was a poverty scenario created by globalization through a variety of industrial distribution media to extract all potentials to benefit an established industry. Finally, consumption culture causes all aspects of life to be a commodity object because the needs that arise will always exceed the production of goods.